FINANCIAL CRISES AS A THREAT TO CORPORATE SUSTAINABILITY: EVALUATING THE IMPLICATIONS OF ASSET DEVALUATION AND DEBT DEFLATION IN THE PURSUIT OF SUSTAINABLE DEVELOPMENT - Goodluck, Happiness Chibuzor; Iliemena, Rachael Okwudili; Islam, Md. Mohidul (International Journal of Accounting & Finance Review, 2022)
In the past few years, economic efforts and policies of nations and businesses have been geared towards achieving sustainability. However, the general price level and other economic factors have not been so favorable for businesses over these years, especially in recent times, thus raising many questions in the area of sustainability of operations. Consequently, we examined the extent to which financial crises (measured by asset devaluation and debt deflation) threaten corporate survival using the case of selected Nigerian manufacturing companies. This descriptive study’s population was 83 operations staff of selected manufacturing firms. Data for the study were gathered from 69 respondents who formed the study’s sample. Pearson Product Moment Correlation was used as the procedure for data analyses, and evidence showed that asset devaluation and debt deflation significantly threaten firm liquidity and re-investment capabilities of manufacturing firms. This paper, thus, concluded that financial crises pose a significant threat to corporate sustainability. As a way forward, corporate organizations, especially those in the manufacturing business, should endeavor to maintain moderate capital and debt ratio while striving for survival to avoid the threats to liquidity and earnings re-investments; at the same time, national and state governments are encouraged to urgently institute measures to cushion the business effects of the financial crises as a further move to sustainable development. JEL Classification Codes: G01, Q01, G12, F31, F41.